EDUCAÇÃO AMBIENTAL NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: CONTRIBUIÇÕES DE PIAGET E VYGOTSKY À LUZ DA COMPLEXIDADE - PERETIATKO, JOCIMARA (2022)
As a result of the serious degradation of the environment in the recent decades, Environmental Education (EE) emerges as an alternative to face this scenario by seeking to transform the society-nature relationship. The documents that guide EE recommend that it must be developed from a critical perspective, in an interdisciplinary way, at all levels and modalities of education, including the early years of elementary school in which the student begins the process of literacy and social contact. To work with this age group, it is necessary to consider how child development and learning occurs, and authors, such as Piaget and Vygotsky, bring numerous contributions. Although at first glance such theorists seem to be opposites, in which Piaget values more the individual and biological aspect of being and, Vygotsky, the social aspect, we consider that such authors can be complementary from Morin's Complexity Theory. This perspective brings a vast theoretical framework for an integrative and differentiated interpretation of reality. Our objective was to investigate to what extent it is possible to work on EE in the early years of elementary school from the approximation between Piaget and Vygotsky through Morin, to then develop and evaluate a paradidactic material for the initial years, which approached EE from the perspective of complexity, in dialogue with the theories of Piaget and Vygotsky. This research was carried out under a qualitative approach from a bibliographical and descriptive perspective. A focus group with graduate students majoring in the masters of PPGEn-UNICENTRO, and a questionnaire applied to Elementary school teachers from Goioxim-PR, were used for data collection. Bardin's (2011) content analysis was the reference to analyze data. The results revealed the possibility for the teacher of the early years to teach EE in a complex perspective in a transdisciplinary way, having as support the material "Re-reading of school garden practices, waste sorting and recyclable toys from a complex approach to Environmental Education". In relation to its evaluation, some of the contributions cited by the subjects (master's students and teachers) refer to the theory-practice approach, the possibilities of building didactic sequences and using them for other education levels. It is believed that the teacher supported by Piaget and Vygotsky will be able to approach EE beyond the critical perspective, that is, a complex EE that is more suited to elementary school children.